Sequence-based species delineation and molecular phylogenetics of the transitional Nearctic–Neotropical grasshopper genus Taeniopoda (Orthoptera, Romaleidae). Issue 6 (2nd November 2017) - De JesÚs-Bonilla, Vladimir Salvador; Barrientos-Lozano, Ludivina; ZaldÍvar-RiverÓn, Alejandro
Abstract : Taeniopoda is a genus of grasshoppers currently represented by 12 species distributed from southern USA to Panama, with most of them occurring along the transitional Nearctic–Neotropical region in central and southern Mexico. Despite being a small group of conspicuous, colourful species, the systematics of Taeniopoda has been largely neglected, including its phylogenetic affinity with the morphologically similar, monotypic genus Romalea . Here, we assessed the species limits in 11 of the species of Teniopoda based on two mitochondrial (mt) markers (COI, cyt b ). Phylogenetic relationships were reconstructed adding two nuclear gene markers (28S, H3). A relaxed molecular clock analysis was performed based on the mt markers. We detected nuclear mt paralogues ( numts ) and the probable introgression of T. tamaulipensis mtDNA in specimens of T. eques from central Mexico. Between six and 14 species of Taeniopoda were delimited by the sequence-based approaches performed (COI divergence with thresholds of 1 and 2%; General Mixed Yule-Coalescent (GMYC) model). The GMYC and 1% threshold analyses with COI were more congruent with the currently recognized morphology-based taxonomy with 10 and 11 putative species, respectively. Four of these species were regarded as 'stable', since they were supported by at least one of the molecular analyses and by diagnostic morphological features. The species-based phylogeny recovered Taeniopoda as paraphyletic with respect to the monotypic genus Romalea . Three morphologically and geographically congruent major clades were recovered, two with species having a considerably elevated pronotal crest and one with its members having it less elevated. The origin and subsequent diversification of Taeniopoda were estimated to occur from the mid and late Miocene to Pliocene, respectively. The current species diversity in Taeniopoda was estimated to occur during the Pleistocene, which was probably influenced by the climatic oscillations that occurred during this period and the uplift of mountain ranges in Central America.